Mytilus edulis foot protein mimics for tailoring long-acting endothelium-mimicking anti-thrombotic surfaces - Zeyu Du; Yuting Huang; Qing Ma; Wentai Zhang; Yan Fu; Nan Huang; Xin Li; Zhilu Yang; Wenjie Tian (Bioactive Materials)
Surfaces with enduring and superior antithrombotic properties are essential for long-term blood-contacting devices. While current surface engineering strategies integrating anticoagulants and antiplatelet agents show promise in mimicking the non-thrombogenic properties of the endothelium, their long-term effectiveness remains limited. Here, we report an easy-to-perform, dual-biomimetic surface engineering strategy for tailoring long-acting endothelium-mimicking anti-thrombotic surfaces. We first designed a Mytilus edulis foot protein-5 (Mefp-5) mimic rich in amine and clickable alkynyl groups to polymerize-deposit a chemical robust coating onto the surface through a mussel-inspired adhesion mechanism. Then, a clickable nitric oxide (NO, an antiplatelet agent)-generating enzyme and the anticoagulant heparin were sequentially co-grafted onto the chemical robust coatings via click chemistry and carbodiimide chemistry. Our results demonstrate that this engineered surface achieved an impressive NO catalytic release efficiency of up to 88 %, while heparin retained 86 % of its bioactivity even after one month of exposure to PBS containing NO donor. Both in vitro and in vivo experiments confirmed that this robust endothelium-mimicking coating substantially reduces thrombosis formation. Overall, our long-acting endothelium-mimicking anti-thrombotic coatings present a promising and feasible strategy to address thrombosis-related challenges associated with blood-contacting devices.